A preliminary study on species composition of zoobenthos on the lower section of Hieu river, Quang Tri province - Trung, Hoang Dinh (Academia Journal of Biology, 2012)
The main objective of this study was to research species composition zoobenthos on the lower section of Hieu river, Quang Tri province. The study was carried out from October of 2011 to May of 2012. The paper repated, 43 species of zoobenthos belonging to 29 genera, 16 families recorded. Of the zoobenthos, the Crustacea were the most abundant with 18 species, 11 genera and 4 families; the Polychaeta with 2 species, 2 genera and 2 families; the Olygochaeta with 3 species, 2 genera and 2 families; the Gastropoda with 12 species, 11 genera, 5 families; the Bivalvia with 8 species,  3 genera, 3 families.